Studying mathematics teachers interactions with curriculum materials through different lenses: Towards a deeper understanding of the processes at stake. (2019) - Trouche, Luc; Gitirana, Verônica; Miyakawa, Takeshi; Pepin, Birgit; Wang, Chongyang
Highlights: Understanding teachers interacting with resources when preparing a new lesson. The case of two mathematics French teachers facing an important curriculum change. Complexity of these interactions revealing, and developing teachers' knowledge. Interest of analyzing these interactions from different theoretical perspectives. Abstract: In this study we explore the interactions between teachers and resources during lesson preparation from different perspectives. We ask in which ways the crossing of perspectives help to develop deeper understandings of teacher interactions with curriculum resources. For doing this, we have chosen the following three theoretical frames: (1) Documentational Approach to Didactics (DAD); (2) Anthropological Theory of the Didactic (ATD); and (3) Cultural-Historical Activity Theory (CHAT). We chose data concerning two experienced mathematics teachers (at lower secondary school level) working together, preparing lessons on the topic of "algorithmics", a topic newly introduced in grade 6 of the French curriculum, and hence a topic they had never taught before.